Reviewing gender and cultural factors associated with HIV/AIDS among university students in the South African context - A. van Staden; G. Badenhorst (AOSIS, 2009)
South Africa is in the midst of a catastrophic AIDS epidemic. HIV prevalence statistics in most countries indicate that up to 60% of all new infections occur among 15 to 24 year olds, whilst this group also boasts the highest incidence of sexually transmitted infections (STIs). Statistical findings among South African students predict a 10% increase in the HIV infection rate, highlighting the inability of universities to cope with societies' demands for academically trained workers which, in the near future, will have a detrimental effect on the economy of South Africa. From the literature it is evident that HIV/AIDS is more than a health issue, it is an inter-sectoral challenge to any society. This paper explored the interplay of gender and cultural factors on South African students' sexual behaviour by inter alia discussing the following factors that might put students at risk for HIV infection: male dominance vs. female submissiveness; age of first sexual encounter; gender-based violence; contraception; circumcision; financial status; myths and 'othering'; demonstrating the need for effective strategies, policies and programmes to protect young people, especially females from sexual abuse/rape and its consequences, including HIV. The literature review revealed that South African students, despite adequate HIV/AIDS knowledge, demonstrated high rates of sexual practices that place them at risk for HIV infection, i.e. unprotected sex, multiple partners and 'sugar-daddy practices'. The paper concludes with a discussion on recommendations for future HIV prevention/ intervention programmes, highlighting the fact that it acquires an inclusive approach. Such interventions should move beyond the individual level to be effective and target gender-based inequalities, human rights violations, including sexual violence and rape, as well as stigma and poverty reduction, both at community and tertiary educational level.